2019
DOI: 10.3390/clockssleep1030032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Circadian Entrainment in Mice and Its Utility under Human Shiftwork Schedules

Abstract: The circadian system is generally considered to be incapable of adjusting to rapid changes in sleep/work demands. In shiftworkers this leads to chronic circadian disruption and sleep loss, which together predict underperformance at work and negative health consequences. Two distinct experimental protocols have been proposed to increase circadian flexibility in rodents using dim light at night: rhythm bifurcation and T-cycle (i.e., day length) entrainment. Successful translation of such protocols to human shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…26,27 Here, we find supporting evidence that napping on day shift is relatively common, as is adoption of the two strategies for night shifts that involve napping, either regularly (Nap Proxy) or before the first night shift only (Switch Napper). Independent of the benefits of napping from a sleep homeostat perspective, as well as limited evidence that polyphasic sleep can be as good as a single bout of sleep by some measures, [51][52][53][54] it has been theorized that a bifurcated waveform might be advantageous for shiftworkers; 55,56 however, as in the case of the compromise phase position, this would be the case only if the underlying pacemaker truly adapted to the light schedule. Such a feat would be difficult to achieve outside of laboratory settings, and would require the use of blue-blocking glasses, scheduled natural light, and other aids for light modulation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Here, we find supporting evidence that napping on day shift is relatively common, as is adoption of the two strategies for night shifts that involve napping, either regularly (Nap Proxy) or before the first night shift only (Switch Napper). Independent of the benefits of napping from a sleep homeostat perspective, as well as limited evidence that polyphasic sleep can be as good as a single bout of sleep by some measures, [51][52][53][54] it has been theorized that a bifurcated waveform might be advantageous for shiftworkers; 55,56 however, as in the case of the compromise phase position, this would be the case only if the underlying pacemaker truly adapted to the light schedule. Such a feat would be difficult to achieve outside of laboratory settings, and would require the use of blue-blocking glasses, scheduled natural light, and other aids for light modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used non-24-hr T-cycles with two separate light-dark periods (LDLD cycles), referred to as bifurcation, which disrupts circadian photoentrainment and results in the alignment of activity rhythms to the two periods of darkness and does not induce circadian arrhythmia when exposed to constant dark conditions [13,31,33]. Although the achievement of bifurcation is regarded as advantageous for the adaptability of activity rhythms to extreme changes to the 24hr solar cycle (jet lag, shiftwork, space travel), considering bifurcation as a therapeutic option for daily adaptability requires the context of the solar day [34,35]. Additionally, authors studying bifurcation including Gorman and Elliot, reported that sudden or gradual exposure to T18 or T30 yielded no difference in the ability of animals to achieve bifurcated rhythms [12,13,31,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Although the achievement of bifurcation is regarded as advantageous for the adaptability of activity rhythms to extreme changes to the 24hr solar cycle (jet lag, shiftwork, space travel), considering bifurcation as a therapeutic option for daily adaptability requires the context of the solar day [34,35]. Additionally, authors studying bifurcation including Gorman and Elliot, reported that sudden or gradual exposure to T18 or T30 yielded no difference in the ability of animals to achieve bifurcated rhythms [12,13,31,33,34]. These studies on bifurcation are different from the current study which shows how a gradual, not sudden, exposure to 4 LD cycles within 24 hours (LDLDLDLD: quadfurcation), leads to circadian arrhythmia in constant dark conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extended upper range of entrainment in nLAN is not explicable in terms of a proportionately increased delay portion of the light pulse PRC, nor a sufficiently large lengthening of free-running period (beyond the 0.3 h effect described above). Phase angles in dim-facilitated entrainment in non-24 h lighting conditions do not consistently follow the patterns predicted by relative length of the LD-cycle and the FRP, suggesting more complex entrainment mechanisms must play a role (19,104,112,120). In addition, the acceleration of re-entrainment following simulated jetlag, which occurs for phase advances and delays of various sizes, cannot be explained by changes in free-running period without concomitant changes in the PRC amplitude.…”
Section: Extreme Entrainment: T-cycles and Bifurcationmentioning
confidence: 94%
“…Both of these consequences of nLAN -enhanced T-cycle entrainment and behavioral rhythm bifurcation -cannot be explained by simple masking (19,104,106,(110)(111)(112)(113)(114)(115)(116)(117)(118)(119). By the same token, neither entrainment pattern is readily understood by non-parametric entrainment theory that accurately models entrainment to more traditional experimental regimens.…”
Section: Extreme Entrainment: T-cycles and Bifurcationmentioning
confidence: 99%